Mid-term outcomes of patients with Lotus and Evolut transcatheter valves - Hájek, Petr; Polaková, Eva; Adlová, Radka; Horváth, Martin; Hansvenclová, Eva; Pecková, Monika; Veselka, Josef (Postępy w Kardiologii Interwencyjnej, 2022)
Introduction: Long-term data on the Lotus® (Boston Scientific, USA) valve are lacking. Aim: To evaluate mid-term outcomes of aortic stenosis patients treated with either Lotus or Evolut R® valves (Medtronic, USA). Material and methods: Our study sample comprised 190 patients (71 Lotus and 119 Evolut valves). The mean clinical follow-up was 2.0 ±0.9 years. Information on mortality was obtained from the National Institutes of Health Information and Statistics. Results: No significant differences existed in baseline characteristics between the groups. The rate of procedural complications was low and without significant differences between groups. The log rank test showed higher mortality in the Lotus group for cardiovascular mortality (p = 0.02; RR = 2.4, 95% CI: 1.123-5.075). Multivariable analysis revealed that the Lotus valve was independently associated with cardiovascular mortality (p = 0.03). At the end of echocardiography follow-up (4.1 ±0.9 years), we found a significantly higher mean aortic valve gradient (AVGm) in the Lotus group than in the Evolut group (17.9 ±9.5 vs. 10.2 ±3.5 mm Hg; p = 0.0006), and 3 (10%) patients from the Lotus group suffered from symptomatic re-stenosis requiering re-intervention. Conclusions: The results of our study suggest that higher cardiovascular mortality rates during mid-term follow-up were associated with Lotus compared with Evolut valves. Higher AVGm in the Lotus valves suggests the possibility of accelerated prosthesis degeneration.